Retrocecal hernia successfully treated with laparoscopic surgery: A case report and literature review of 15 cases in Japan - Sasaki, Kazuhito (Int J Surg Case Rep, 2015)
INTRODUCTION: Retrocecal hernia is rare and involves strangulation ileus, and therefore, frequently requires emergency surgery following conservative therapy. PRESENTATION OF CASE: We report an interesting case of a retrocecal hernia in a 65-year-old man, with a history of diabetes mellitus. The patient was admitted to our hospital with severe periumbilical pain and nausea. Abdominal computed tomography revealed an intestinal obstruction at a pericecal site, and dilatation of the small bowel at the oral side of the obstruction. The patient was initially treated with conservative therapy using long intestinal tube placement. On the 12th hospital day, the patient’s symptoms had not resolved, and laparoscopic surgery was performed. We diagnosed a retrocecal hernia based on laparoscopic findings and repaired it. The patient was discharged without complications on the 7th postoperative day. DISCUSSION AND CONCLUSION: Using laparoscopic exploration and suturing, we were able to perform a minimally invasive operation that may have promoted an earlier hospital discharge.